Marketing Strategy Analysis in Increasing the Decision to Become a Life Insurance Customer at PT. AIA Chandra Utama Agency - Katarina; Yosefina K.I.D.D Dhae; Dominikus K.T Aman (Journal of Management and Business Innovation, 2026)
This study aims to analyze the marketing strategy implemented by PT. AIA Chandra Utama Agency and the supporting and inhibiting factors of the marketing strategy in increasing the decision to become a life insurance customer. This research uses a qualitative descriptive method. The informants consisted of 1 leader, 5 agents, 5 customers, and 5 non-customers, totaling 16 informants. Data collection techniques were conducted through interviews, observation, and documentation. Data analysis used an interactive model including data reduction, data presentation, and conclusion drawing. PT. AIA Chandra Utama Agency implements targeted marketing strategies through market segmentation, target market selection, and market positioning. The company also applies direct selling, earned media through social media, and point of purchase strategies through public events. The company applies the service marketing mix (7P) including product, price, place, promotion, people, process, and physical evidence. This research contributes to service marketing theory by strengthening understanding of marketing strategy implementation in the life insurance industry in Eastern Indonesia, an underexplored context. It expands the marketing mix concept in relation to customer decisions in the Eastern Indonesian cultural context. The findings provide input for companies to evaluate and improve marketing strategies, and serve as consideration for designing more effective strategies according to the characteristics of the Kupang City community. The research is limited to one agency in Kupang City using a qualitative approach, so results cannot be generalized. Future research could compare multiple insurance companies or use quantitative methods.